Effect of Digital Financial Inclusion on Dredging the Path of Green Growth—New Evidence From Front-End and Back-End Perspectives - Cao, Jianhong; Law, Siong Hook; Wu, Desheng; Tang, Xianghua; Yang, Xiaodong (Frontiers in Environmental Science, 2022)
To dredge China's green growth path, this paper analyzes the front-end and back-end factors affecting green growth and also investigates the mediation role of digital financial inclusion from different dimensions. This study employs China’s provincial panel data in 2011-2018 and uses the dynamic threshold model to study the threshold effect of technological progress (TP) on green growth (GG) and the threshold effect of green growth (GG) on floating population (FP). The empirical results show that: first, with the digital financial inclusion as the threshold variable, there is a nonlinear relationship between technological progress (TP) and green growth (GG); second, with digital financial inclusion as the threshold variable, there is a nonlinear relationship between green growth (GG) and floating population (FP); third, output biased technological progress needs more support from digital financial inclusion than input biased technological progress than can significantly promote green growth. From the dimension of “digitization+financial scale+inclusion”, digital financial inclusion not only improves the positive effect of technological progress on green growth but also alleviates the negative effect of green growth on the floating population. This study makes up for the research gap in the back-end impact of green growth based on new ideas of digital financial inclusion and floating population and has important theoretical reference significance for removing the obstacles in the green development path and realizing sustainable green growth.